Mitigation of Salinity Stress in Soybean Using Organic Amendments - Ferdous, J; Mannan, MA; Haque, MM; Alam, MS; Talukder, S (Bangladesh Agronomy Journal, 2018)
A pot experiment was carried out in semi-controlled condition at the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur from November 2015 to March 2016 to assess the effect of organic amendments to mitigate salinity stress in Soybean var. BARI soybean 5. Two types of organic amendments i) water hyacinth compost and ii) rice husk biochar were mixed in soil @ 5 and 10 t ha-1 of both. Saline solution was prepared by adding tap water in seawater to make 5 and 10 dS m-1 salinity respectively. Plants were irrigated with the salt solution from 14th day after sowing (DAS) to maturity and the control plants were irrigated with tap water. Data on different parameters like plant height, leaf, stem, root dry matter and yield contributing parameters were recorded at harvest. Experimental results revealed that salinity decreased plant height, dry weight of leaf, stem and root as well as yield of soybean plant-1. Application of water hyacinth compost and rice husk biochar had positive effects on mitigating the negative effects of salinity stress on all those parameters studied. However, rice husk biochar at the rate of 5 t ha-1 showed best result to mitigate salinity stress at low salinity (5 dSmdS m-1 condition. Bangladesh Agron. J. 2018, 21(1): 39-50